PENERAPAN APLIKASI SISTEM INFORMASI PENERIMAAN TUNJANGAN PROFESI GURU PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI NUSA TENGGARA TIMUR - Iriane, Gregorius Rinduh (STIKOM Uyelindo Kupang, 2021)
Computer applications have a very important role in life in today's modern society. Technology that develops according to the demands of the times is expected to be a supporting tool to deal with problems that arise in managing and solving problems that exist in the company or organization. Likewise, the Regional Office of the Ministry of Religion of the Province of East Nusa Tenggara, especially in the section on Islamic Religious Education, is expected to provide precise and accurate information in processing the data for teachers receiving certification. This application is designed in such a way as to make it easier to process data on receiving teacher certification allowances at the Regional Office of the Ministry of Religion in East Nusa Tenggara Province to be faster, more precise, and efficient. This application is dynamic, meaning that the information provided can change at any time based on the current situation. The results of the application of the Application for Accepting Professional Allowances (Certification Allowances) for Teachers are to assist the office so that the process of collecting data on teachers receiving certification allowances can be easily, quickly, and efficiently.